2008
DOI: 10.1074/jbc.m803095200
|View full text |Cite
|
Sign up to set email alerts
|

Weak Organic Acids Trigger Conformational Changes of the Yeast Transcription Factor War1 in Vivo to Elicit Stress Adaptation

Abstract: The Saccharomyces cerevisiae zinc cluster regulator War1 mediates an essential transcriptional and adaptive response to weak organic acid stress. Here we investigate the mechanism of War1 activation upon weak acid stress. We identified several gain-of-function WAR1 alleles mapping to the central War1 region. These mutations constitutively increase levels of the plasma membrane ABC transporter Pdr12, the main War1 target mediating stress adaptation. Functional analysis of War1 reveals that the central region an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…Attempts to assign a regulatory function to weak acid induced changes of the War1 phosphorylation status, which results in a robust migration difference, were unsuccessful (Frohner et al, 2010; Mollapour and Piper, 2012). It has been suggested that War1 becomes directly activated by weak acids triggering conformational changes (Gregori et al, 2008). In addition, adaptation to weak acids also requires Haa1, a further weak acid inducible transcription factor S. cerevisiae (Fernandes et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to assign a regulatory function to weak acid induced changes of the War1 phosphorylation status, which results in a robust migration difference, were unsuccessful (Frohner et al, 2010; Mollapour and Piper, 2012). It has been suggested that War1 becomes directly activated by weak acids triggering conformational changes (Gregori et al, 2008). In addition, adaptation to weak acids also requires Haa1, a further weak acid inducible transcription factor S. cerevisiae (Fernandes et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…1.63 Preservation of cheeses, jams, and fish products Gregori et al, 2008;Abbot et al, 2007;Makrantoni et al, 2007Schuller et al, 2004Mollapour et al, 2004;Mollapour et al, 2006Hatzixhantis et al, 2003Kren et al, 2003;Pearce et al, 2001;Piper et al, 1999;Holyoak et al, 1996;Holyoak et al, 1999 Lactic acid 3.86…”
Section: 71mentioning
confidence: 99%
“…Preservation of bakery and fresh dairy products Mira et al, 2009;Gregori et al, 2008;Mollapour and Piper, 2007;Abbot et al, 2007;Fernandes et al, 2003;Simõ es et al, 2006;Piper et al, 1998, Kren et al, 2003 Octanoic acid 4.89…”
Section: à032mentioning
confidence: 99%
“…For instance, the expression of the transcription factor encoding gene WAR1 (involved in weak acid resistance) and of its main target gene PDR12 decreased in the dhh1 mutant. Noteworthy, the level of expression of DHH1 increased in a WAR1 gain of function mutant [87]. Similarly, Dhh1 apparently controls the level of expression of several proteins regulating mRNA stability, including for instance PUF2 and PUF3 .…”
Section: Discussionmentioning
confidence: 99%